1999
DOI: 10.1002/(sici)1521-3773(19991216)38:24<3650::aid-anie3650>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

“Figure Eight” Cyclooctapyrroles: Enantiomeric Separation and Determination of the Absolute Configuration of a Binuclear Metal Complex

Abstract: The hypothesized racemate separation of cyclooctapyrroles with chiral figure eight conformations-and of metal complexes derived from these ligands-has been realized. The cyclooctapyrrole 1 (as hexadecaethyl derivative), which according to NMR analysis exhibits restricted mobility, and its binuclear palladium and copper complexes could be separated into stable enantiomers by preparative chromatography on a chiral phase. In the case of the palladium complex and the free ligand 1 it was also possible to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
1
4

Year Published

2000
2000
2007
2007

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 133 publications
(71 citation statements)
references
References 2 publications
2
64
1
4
Order By: Relevance
“…[19,20] Ligand 3 gave only some homodinuclear complexes according to published procedures. [20,21] The electrochemical measurements were carried out in a glove box (less than 3 ppm of H 2 O and less than 2 ppm of O 2 ) at room temperature (25Ϯ2°C) in PhCN containing 0.1  Bu 4 NPF 6 in a classical three-electrode cell. The electrochemical cell was connected to a computerised multipurpose electrochemical device (PAR 273) interfaced with a PC computer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[19,20] Ligand 3 gave only some homodinuclear complexes according to published procedures. [20,21] The electrochemical measurements were carried out in a glove box (less than 3 ppm of H 2 O and less than 2 ppm of O 2 ) at room temperature (25Ϯ2°C) in PhCN containing 0.1  Bu 4 NPF 6 in a classical three-electrode cell. The electrochemical cell was connected to a computerised multipurpose electrochemical device (PAR 273) interfaced with a PC computer.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, only homodinuclear complexes could be obtained and identified with ligand 3. [21] Until now, electrochemical investigations of macrocyclic polypyrroles containing more than four pyrrole units remain rather scarce, [17] and studies on octapyrrolic macrocycles are restricted to preliminary studies on the free bases and some complexes of 1 and 3 in CH 2 Cl 2 . [22] In the present paper the electrochemical behaviour of a new series of cyclooctaphyrins, namely 2, has been investigated in dry benzonitrile.…”
Section: Introductionmentioning
confidence: 99%
“…This assignment is further supported by the recent findings by Vogel et al, who reported the same relationship between the sign of the Cotton effect and the helicity of the ligand for a (cyclooctaphyrinato)dipalladium. [34] The fact, that the maxima of the major CD and UV/Vis absorptions are found at the same wavelength (432 nm), is indicative of a strong electronic coupling, i.e. π-conjugation of both dipyrrin units in 14, and is also found for biliverdin and other one-chromophore systems.…”
Section: Enantioseparation Of 14mentioning
confidence: 99%
“…Erst damals veröffentlichte die Arbeitsgruppe von Sessler die Synthese des Decapyrrolmakrocyclus 4, den man wegen seiner tief türkisfarbenen Lösung Turcasarin nannte. [6] Bei der Synthese von 4 wurde ein Bipyrroldialdehyd 5 mit einem Terpyrrol 6 in Gegenwart einer Säure als Katalysator in einer Art MacDonald-Kondensation [7,8] [13,14] Die Einzelheiten sind hier zwar noch nicht publiziert, doch die elektrochemischen Eigenschaften dieser Metallooctaphyrine wurden untersucht. [13] Alle erwähnten Octaphyrine liegen ebenso wie Turcasarin 4 in chiralen 8er-Konformationen vor und sollten daher prinzipiell in ihre Enantiomere trennbar sein, was für 12 und das damit verwandte Tetrahydrooctaphyrin 11 vor kurzem tatsächlich gelang.…”
Section: Sapphyrin Pentaphyrinunclassified